FORMATION OF LEXICAL COMPETENCE OF UNIVERSITY STUDENTS IN THE CONTEXT OF LINGUISTIC TERMS - Pardayeva, Diyora (Журнал иностранных языков и лингвистики, 2021)
This article discusses the issue of the formation of foreign language lexical competence of university students, reveals the basic concepts related to the lexical side of teaching a foreign language. It pays attention to lexical skills in the context of linguistic terms as a structural component of foreign language lexical competence, which involves taking into account the linguistic features of the language material, as well as the educational and cognitive activities of students.